Mitigation of the greenhouse effect by solar cells penetration based on the genetic algorithm - H. Alkhersan, Ibrahim; Falah Fakhruldeen, Hassan (International Journal of Engineering and Technology, 2018)
Over the previous decade, global warming from greenhouse gas growth has become a significant science and political Over the previous decade, global warming from greenhouse gas growth has become a significant science and political problem. That infrared radiation is captured in a global atmosphere by greenhouse gasses, and that makes the CO2 levels have risen by about 25 percent since 1850 due to the combustion of fossil fuel in the ambient. Besides that, the concentrations of other trace greenhouse gasses such as methane and chlor-ofluorocarbons have risen even more. Global warming harms humanity and the planet together. Outcomes from the latest climate change researches showed there is increasing in the temperature during the next century by about 2Â° to 6Â°C. Sea levels are typically projected to rise from 0.5 to 1.5 meters for the next century, but there is little likelihood of significant or even harmful change. One of the great solutions to moderate global warming is by reduction the current consumed by the consumers from the generation power stations. The decline comes as a result of using nonconventional energy sources like the solar energy that installed in homes to participate in feeding the home's loads besides the current consumed from the secondary distribution transformers. The GA used in this paper to ensure all the PVs used in an efficient way that not causes any stability problem in the secondary distribution network.Â Â Â